Proactive Behavior Drives Strategic Capacity Building in Baghdad Hotels - Salah Mahdi Akfour (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Strategic capabilities are essential for organizations operating in dynamic environments. Specific Background: Hotels in Baghdad face limitations in strategic capabilities and the adoption of proactive behavioral practices. Knowledge Gap: Limited evidence exists regarding the relationship between proactive behavior and strategic capacity building in the Iraqi hotel sector. Aims: This study examines the role of proactive behavior in building strategic capabilities in selected hotels in Baghdad. Results: Based on data from 40 hotel leaders, the findings indicate a significant relationship between proactive behavior and strategic capacity building. Individual innovation, personal initiative, and responsibility-taking contributed substantially to capability development, while proactive personality showed a relatively limited contribution. Novelty: The study integrates the dimensions of proactive behavior and strategic capabilities within the context of Baghdad hotels. Implications: Strengthening proactive behavioral practices can support cognitive, absorptive, and transformational capabilities, thereby improving organizational competitiveness and development. Highlights: • Significant association was identified between proactive behavior dimensions and strategic capability development in Baghdad hotels.• Individual innovation and responsibility-taking emerged as major contributors to organizational capability formation.• Personal initiative supported the development of cognitive, absorptive, and transformational capacities within hotel organizations. Keywords: Proactive Behavior, Strategic Capabilities, Individual Innovation, Personal Initiative, Hotel Management